Prehabilitation: The Impact of Preoperative Exclusive Enteral Nutrition on Paediatric Patients With Crohn Disease. Issue 4 (April 2020) - Harris, Rachel E.; Duncan, Hazel; Buchanan, Elaine; Cardigan, Tracey; Garrick, Vikki; Curtis, Lee; Gervais, Lisa; Barclay, Andrew; Haddock, Graham; Hansen, Richard; Tayler, Rachel; Walker, Gregor; et al.
Abstract : ABSTRACT: Exclusive enteral nutrition (EEN) is effective in inducing remission in paediatric Crohn Disease (CD) and has been shown to reduce inflammation and improve outcomes in adult CD patients when used before resectional surgery. This retrospective study demonstrates that preoperative EEN is achievable in paediatric CD patients undergoing right hemicolectomy and is associated with positive peri-operative outcomes. Seventeen patients (8 who received preoperative EEN and 9 who did not) were included in the study. Six of 8 (75.0%) managed EEN orally; 1 via nasogastric tube and another via a previously sited gastrostomy. Use of preoperative EEN was associated with a decreased rate of moderate/severe disease on resection pathology (5/8 [62.5%] vs 9/9 [100%]; P  = 0.04). Larger studies are required to determine the wider potential benefits of preoperative EEN on postoperative outcomes within paediatric practice. Abstract : Supplemental Digital Content is available in the text